Use of Jugular Venous Pressure to Optimize Outcomes of Vestibular Schwannoma Resection: A Review of the Literature and Proof of Concept - Brakel, Benjamin; Wang, Jessica; Kam, Jeremy; Huttunen, Henrik; Dhaliwal, Bali; McEwen, Jon; Westerberg, Brian; Makarenko, Serge; Akagami, Ryojo (Journal of Neurological Surgery Part B: Skull Base, 2024)
Background Surgical resection of vestibular schwannoma (VS) and other benign posterior fossa tumors is often curative if gross total resection is achieved; however, these lesions pose unique challenges due to their intricate location and proximity to critical structures. Approaches for resection often utilize lateral head rotation and neck flexion to optimize the surgical field. However, this may inadvertently occlude cerebral venous drainage, elevating intracranial pressure (ICP) and increasing intraoperative bleeding, potentially increasing the operative risk to patients.Methods We review relevant literature regarding the effects of head rotation and neck flexion on internal jugular vein (IJV) occlusion and ICP and highlight the notion that head rotation and flexion may occlude the ipsilateral IJV, increasing ICP. Subsequently, we propose a novel technique using continuous, real-time monitoring of jugular bulb pressure (JBP) to detect obstructions in jugular venous flow and guide optimal head positioning prior to VS resection.Results As proof of concept, we present a single-patient case in which JBP monitoring was employed to optimize head positioning prior to a VS resection, which shows a significant reduction in JBP compared with traditional positioning.Conclusion This innovative approach offers promise in enhancing the safety and efficacy of intracranial surgery for VS and other neurosurgical procedures.
Keywords: head positioning; intracranial pressure; jugular bulb; vestibular schwannoma